Influência de diferentes tipos de estacas e substratos na propagação assexuada de hortênsia [Hydrangea macrophylla (Thunb.) Ser.] - Luz, Petterson Baptista da [UNESP]; Paiva, Patrícia Duarte de Oliveira; Landgraf, Paulo Roberto Corrêa (Editora da Universidade Federal de Lavras (UFLA), 2007)
A hortênsia (Hydrangea macrophylla) é um arbusto semilenhoso de 1,0 a 2,5 m de altura, de folhagem e florescimento decorativos, muito utilizados como flor de vaso e planta para paisagismo. Conduziu-se este trabalho com o objetivo de estudar o enraizamento de estacas de três partes da planta: apical, mediana e basal; em três tipos de substratos: terra, areia e vermiculita, para a formação de mudas. As estacas foram retiradas das plantas matrizes e divididas em segmentos apical, mediano e basal, os quais foram colocados para enraizar em bandejas de isopor, nos substratos areia, terra e vermiculita, em estufa com nebulização. As estacas que apresentaram melhor qualidade de raízes foram as originadas da parte basal do ramo, sendo que o melhor enraizamento foi observado nas estacas colocadas em areia. As estacas obtidas de diferentes partes da planta não se diferenciaram quanto à porcentagem de enraizamento e quanto ao número de brotos formados. Já os substratos que proporcionaram o maior número de brotações foram a areia e a terra. Algumas estacas apresentaram formação de flores, ocorrendo com maior freqüência nas estacas apicais, sem efeito dos substratos. A areia foi o substrato que proporcionou os melhores resultados quanto à qualidade das raízes e porcentagem de enraizamento. O substrato terra foi superior apenas para o número de brotos por estaca, porém não diferenciou estatisticamente da areia. Mudas formadas de estaca da parte basal da planta se mostraram com qualidade superior.

The Hydrangea (Hydrangea macrophylla) is a semi-ligneous shrub measuring 1.0m to 2.5m in height with decorative foliage and flat-topped or rounded clusters of white, pink, or blue flowers widely used as vase or pot flower as well as landscaping plant. The objective of this research work was to study the rooting of stem cuttings obtained from three different parts of the plant: apical, median and basal portions of the stems, in three different types of substrate: soil, sand and vermiculite, for production of new cuttings. The stems were cut from the mother plants and subdivided into apical, median and basal segments, which were then placed for rooting in styrofoam trays containing the three different substrates soil, sand, and vermiculite and arranged inside a growth chamber containing nebulization. The cuttings that presented the best root quality were the ones originated from the basal portion of the stem and sand was the substrate that provided best rooting. The cuttings obtained from the different parts of the plant did not differ as far as percent of rooting and number of sprouts formed are concerned. on the other hand, the substrates that provided highest number of sprouts were sand and soil. Some cuttings presented flower formation, with higher frequency on the cuttings from the apical segment, with no effect from substrate. Sand was the substrate that provided the best results concerning quality of roots and rooting percentage. The soil substrate was superior only for the number of sprouts per cutting although it was not statistically different from the substrate sand. Transplants originated from cuttings of the basal portion of the stem were qualitatively superior.
Influence of different types of stem cuttings and substrates on the asexual reproduction of hydrangea (Hydrangea macrophylla) (Thunb.) Ser.
Keywords: Estacas; enraizamento; propagação; hortênsia; Cuttings; reproduction; rooting